Pattern of Skin Diseases at Upazilla Level - Hoq, Abu Jafar Md Shahidul; Rahman, Gazi Md Matiur; Sultana, Fahmida; Hasan, Mahmudul (Community Based Medical Journal, 2017)
Skin the largest organ in the human body plays a vital role in one's health care. This anatomical barrier regulates the body temperature and interface with the environment for protecting the body against pathogens. The type of skin problems varies in different geographical areas, climate, economic and other factors including personal characteristics such as age and sex. The pattern of skin diseases varies from one area to another and across different parts within the same country. A retrospective study was done among patient attending Upazilla health complex, South Matlab OPD during the period January 2014 to 31 Dec 2014. To determine the pattern of skin diseases seen in a rural upazilla community. All patients attending the Skin & VD outpatient department were included in this study. All those with dermatological complaints were examined in detail, brief relevant history was elicited and clinical diagnosis was made by a consultant dermatologist. Patient of Skin diseases comprised 8984 (12 % of total 74870 patients at OPD). The most common age group was 11-20 years (36.06%). Infective disorders were found in 62% and non-infective disorders in 32%, of all the dermatological cases. Fungal infections (48.20%) were the most common among infective dermatoses, whereas bacterial infections were 2nd in position. Among the non-infective dermatoses, eczemas were the most common (33.54%) followed by urticaria (23.78%). In our study, higher prevalence of infective dermatoses especially fungal infections was more common at rural upazilla level. Since the placement of dermatologists at Upazilla Health Complexes, non-infective dermatoses were also identified in great numbers e.g. Urticaria, Psoriasis, Lichen planus, Pityriasisalba Polymorphic Light Eruption, and vitiligo. These patients were diagnosed, treated and followed up regularly at primary health care settings. CBMJ 2017 January: Vol. 06 No. 01 P: 08-11